Using Flashcards to Increase Grammar Mastery of MTs Students in Kutai Kartanegara - Samsu Armadi (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study reports the difference of using flashcards and textbooks in teaching grammar for junior school students. The study aimed at examining the hypothesis that read: “flashcards do not improve grammar mastery.” This study used an experimental of post-test only design, implementing an experimental group that received flashcards for the treatments of learning grammar, and the controlled group that received textbooks for learning grammar. The hypothesis testing at p=0.05 and n = 48 indicated that Ho was rejected and the result was significant (t-value = 3.377 and t- table = 1.68). This means flashcards significantly improved grammar mastery. In other words, flashcards as media of teaching grammar is superior than using textbook.